Practice patterns about the role of palliation in veterinary surgical oncology. (21st July 2021) - Di Virgilio, Fabrizio; Belluzzi, Elena; Santos, Marisa; Caraty, Johan; Bongartz, Alexandre; Deneuche, Aymeric
Abstract: Whether surgical palliative therapy is appropriate for oncologic veterinary patients is an increasing concern as pet age increases because of improved care. In this study, an online survey (available for 30 days), comprising 100 questions with structured response options, was administered to 492 diplomates of the European College of Veterinary Surgeons (ECVS). The survey queried the technical, ethical, social, medical, and financial aspects of surgical palliative therapy for oncologic veterinary patients. Responses were received from 155 ECVS diplomates (31.5%, n  = 155/492). Palliative surgery was a relatively common intervention in veterinary oncology, with 50% of respondents ( n  = 77.5/155) indicating that 75%–100% of oncological surgeries performed were palliative. The presence of metastasis was judged as a key determinant when deciding to perform palliative oncological surgery by 41% of the respondents ( n  = 63.5/155). The survey revealed that the most commonly performed procedures in palliative oncological surgery were marginal resection, debulking, and amputation. In contrast to human medicine, palliative limb‐sparing surgery, stent placement, and embolization were rarely used in veterinary settings, mainly because of a general lack of expertise among veterinarians, elevated costs, and recourse to euthanasia. Taken together, the survey results highlight the need for appropriate guidelines in the field of oncological surgery. To establish general guidelines and direct veterinarians towards the most appropriate judgement, understanding how and what veterinary surgeons manage palliative oncological surgery and how they perceive the main ethical, social, medical, and financial concerns are essential. Such guidelines will lead to better care for ailing animals and will facilitate the path to healing for owners.